Esophageal ultrasound with ultrasound bronchoscope (EUS-B) guided transvascular needle aspiration (TVNA). (2019) - Tamburrini, Mario; Gothi, Dipti; Scarda, Angelo; Rinaldo, Claudia; Zampieri, Francesca; Zuccon, Umberto
Abstract: We have described a 67-year-old man, diagnosed to have adenocarcinoma of lung by transvascular approach with esophageal ultrasound using ultrasound bronchoscope (EUS-B). To the best of our knowledge this is the first case where EUS-B has been used for transvascular fine needle aspiration cytology to diagnose lung carcinoma.